Levels of Oxidative Stress in Rats Treated with Calorie Restrictive Treatment and 50% Sucrose Solution - Mukhtar, Diniwati; Amsaka, Azha Azzuna; Pd, Fanny Ratnasari; Royhan, Aan; Ridwan, Karina Ajeng (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
This study aims to analyze the level of stress oxidative with treatment calorie restrictions and administration of sucrose solution. This study was a laboratory experimental study with 12 male white rats (Wistar strain) as subjects for caloric restrictive treatment and 12 rats for 50% sucrose solution. Where each group of rats is determined by the dependent and independent variables. Using the pre-posttest control design, the dependent variable of caloric restriction, and the independent variable malondialdehyde. The dependent variables used were body weight using a scale, fasting blood glucose using a glucometer, and MDA using a UV-Vis spectrophotometer. The independent variable used was the administration of 50% sucrose solution. The data were statistically analyzed by T-test analysis. There was no significant decrease in MDA levels in the caloric restriction treatment rats (p = 0.060), besides that there was a significant difference in body weight in both the control and sucrose groups (p <0.05). There was no significant difference in fasting blood sugar in the control group (p > 0.05) and there was a significant difference in the sucrose group (p < 0.05). There was no significant difference in serum MDA levels in either the control or sucrose groups (p > 0.05). There is an effect of calorie restriction on MDA levels. Also, administration of 50% sucrose solution for 4 weeks had a significant effect on the rats' body weight and blood glucose but did not have a significant effect on serum MDA levels.